Le hangar : de l’abri polyvalent à l’édifice spécialisé, l’avènement d’un emblème architectural de la modernisation agricole - Hervé Cividino (In Situ)
During the XXth century, as farming practices intensified, the hangar became the archetype of farm buildings. Despite efforts made by architects and engineers to conceptualize the evolution, this new age of building gave priority to technical aspects. New building techniques spread to rural areas, encouraged by builders and farmers organizations as well as by the state. In the 60s, more complex structures appeared to match the ongoing specialisation of production processes. Under the effect of the generalisation of hangars, traditional farm buildings were progressively abandoned. The standardisation of rural landscapes and the new architecture of the countryside attest to the success of a unique farming model.